Driving Europe : building Europe on roads in the twentieth century - Schipper, Frank (Technology and European history series, 2008)
This book discusses the intersection of Europe and roads. Today we can hardly imagine life without roads and the automobiles that use them to move around. The vast majority of movements in Europe takes place on the road. Travelers use the car to explore parts of the continent on their holidays and goods travel large distances to reach consumers. Indeed, the twentieth century has deservedly been characterized as the century of the car. The situation looked very different around 1900. People crossing national borders by car encountered multiple hurdles on their way. Technically they imported the.